Acidemia versus Hypercapnia and Risk for Severe Intraventricular Hemorrhage - Zayek, Michael Maurice; Alrifai, Wael; Whitehurst, Richard Marion, Jr.; Kua, Kok Lim; Martino, Anthony; Eyal, Fabien Gabriel (American Journal of Perinatology, 2014)
In extremely low birth weight (ELBW) infants, levels of hypercapnia (Paco2) > 60 mm Hg are considered a risk factor for severe intraventricular hemorrhage (IVH). Since cerebral vasoreactivity depends on arterial pH (apH) rather than Paco2, we hypothesize that the role of mild-to-moderate hypercapnia (45–60 mm Hg) in the occurrence of severe IVH is modulated by the metabolic component of acid–base status. ELBW infants (n = 580, born < 28 wk gestation, and BW < 1,000 g) were separated into “high-base deficit (BD)” (n = 291) and “low-BD” (n = 289) groups if infants' median BD were > 4 mEq/L or ≤4 mEq/L, respectively. Rates of severe IVH were higher in “high-BD” (16%) than “low-BD” (9%) group. Although adjusted risk for severe IVH increased with higher Paco2 and higher BD, apH was the sole predictor of severe IVH. In ELBW infants, higher degree of acidemia, rather than hypercapnia per se, during the first 48 hours of life, is associated with higher occurrences of severe IVH.
Keywords: premature infants; extremely low birth weight infants; permissive hypercapnia; brain injury